ISU PENDEKATAN DI DALAM PENGAJIAN SYARIAH DI MALAYSIA: SATU ANALISIS - Abd Rahim, Rahimin Affandi (Jurnal Syariah, 2019)
The study will scrutinize the issues of methodological approach in the present Syariah studies in Malaysia. Following the introduction, the study will proposed several proposition for the betterment of the syariah studies, which may including, firstly the philosophical approach and its impact upon the Islamic studies. Secondly, the new approach of the utilization of the ilmu Usul al-Fiqh andfinaliy, the employment of the pluralism principles in the Syariah studies.